2021
DOI: 10.2147/eb.s317186
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvasculature in Schizophrenia

Abstract: Purpose: Schizophrenia is associated with alterations in neural structure and function of the retina that are similar to changes seen in the retina and brain in multiple neurodegenerative disorders. Preliminary evidence suggests that retinal microvasculature may also be compromised in schizophrenia. The goal of this study was to determine, using optical coherence tomography angiography (OCTA), whether 1) schizophrenia is associated with alterations in retinal microvasculature density; and 2) microvasculature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…More importantly, based on the diagnostic score, a corresponding visual nomogram was established to enhance its clinical applicability. Consistent with our findings, alterations of above six retinal parameters in psychiatric disorders and their potential clinical roles or pathophysiological impact were more or less revealed in earlier researches ( 27 , 38 , 39 ). To some extent, the retinal parameters mentioned above may be closely related to the development of MDD, which suggests that the corresponding morphological and functional changes in the retina may mirror the pathophysiological alterations of MDD in a timely and reasonable manner.…”
Section: Discussionsupporting
confidence: 93%
“…More importantly, based on the diagnostic score, a corresponding visual nomogram was established to enhance its clinical applicability. Consistent with our findings, alterations of above six retinal parameters in psychiatric disorders and their potential clinical roles or pathophysiological impact were more or less revealed in earlier researches ( 27 , 38 , 39 ). To some extent, the retinal parameters mentioned above may be closely related to the development of MDD, which suggests that the corresponding morphological and functional changes in the retina may mirror the pathophysiological alterations of MDD in a timely and reasonable manner.…”
Section: Discussionsupporting
confidence: 93%
“…The limited number of published studies using OCTA in schizophrenia can be briefly summarized. Our study found that individuals with schizophrenia demonstrated reductions in microvascular density and an increase in foveal avascular zone area compared to controls (30). An illustration of this can be seen in Figure 2.…”
Section: Utility Of Octasupporting
confidence: 56%
“…For instance, if vascular loss were found to precede loss of neural tissue, this may lend evidence toward a more causal relationship. As OCT and OCTA can be performed on the same device, such a research aim is readily feasible, and data from one first episode psychosis sample provides preliminary evidence for vascular changes that precede neural changes (30,37). Moreover, OCTA has been used previously to detect subtle vascular changes in such as radiation retinopathy over time periods as short as 6 months (38).…”
Section: Discussionmentioning
confidence: 99%
“…The small sample sizes, difficulties in interpretation and no unanimous protocols (on parameters that should be taken into account) limit the level of validity of the findings and may lead to false-negative or -positive results. However, in other studies, the sample sizes were similar, for example, 28 patients with SZ in the recent study by Silverstein and colleagues [ 52 ], 30 patients with SSD in the study of Alizedah and colleagues [ 49 ] and 22 patients in the study of Budakoglu and colleagues [ 53 ]. The small sample size corresponded to the lack of differentiation between the gender, disease duration and type of medications taken.…”
Section: Discussionmentioning
confidence: 84%